2019
DOI: 10.1186/s40635-019-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between increased arterial stiffness and clinical outcomes in patients with early sepsis: a prospective observational cohort study

Abstract: Background Conduit arteries, especially the aorta, play a major role in ensuring efficient cardiac function and optimal microvascular flow due to their viscoelastic properties. Studies in animals and on isolated arteries show that acute systemic inflammation can cause aortic stiffening which affects hemodynamic efficiency. Carotid-femoral pulse wave velocity, a measure of aortic stiffness, may be useful as a bedside investigational method in patients with early sepsis admitted to intensive care, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
16
0
3
Order By: Relevance
“…For example, LPS injection in rabbits has been shown to induce a dysfunction of the endothelium-mediated vascular relaxation in the aorta (Leclerc et al, 2000), and additional experimental observations in endotoxin shock swine model confirmed an increased stiffness of the central aorta and, on the opposite, an increase in compliance of the peripheral compartment generated by septic shock (Hatib et al, 2011). Finally, a recent clinical observational study on arterial elastic properties has shown an increase in aortic stiffness, with respect to the general population, in a cohort of septic shock patients when pulse wave velocity (PWV, an indirect measure of arterial stiffness in large arteries) was measured at the time of admission (Kazune et al, 2019).…”
Section: Introductionmentioning
confidence: 64%
“…For example, LPS injection in rabbits has been shown to induce a dysfunction of the endothelium-mediated vascular relaxation in the aorta (Leclerc et al, 2000), and additional experimental observations in endotoxin shock swine model confirmed an increased stiffness of the central aorta and, on the opposite, an increase in compliance of the peripheral compartment generated by septic shock (Hatib et al, 2011). Finally, a recent clinical observational study on arterial elastic properties has shown an increase in aortic stiffness, with respect to the general population, in a cohort of septic shock patients when pulse wave velocity (PWV, an indirect measure of arterial stiffness in large arteries) was measured at the time of admission (Kazune et al, 2019).…”
Section: Introductionmentioning
confidence: 64%
“…Though, the use of SphygmoCor, Mobil-o-Graph PWA and other non-invasive devices in ICU patients has been investigated in previous studies; our study is the first one having as primary endpoint checking the feasibility of these methods in respect to central and peripheral blood pressure estimation and using as comparison the invasive blood pressure values. [11][12][13][14][15] Moreover, unlike previous studies, our study population consisted entirely of patients with septic or cardiogenic shock with the vast majority of them receiving catecholamines and no mechanical assistances such as intra-aortic balloon pump. Non-invasive assessment failure was more pronounced with the SphygmoCor XCEL.…”
Section: Discussionmentioning
confidence: 99%
“…SphygmoCor, Mobil-o-Graph ® 24 hours PWA and other arterial stiffness measuring techniques were applied on ICU (intensive care unit) patients in previous studies. [11][12][13][14][15] However, only a subset of the patients included in these studies were diagnosed with shock or the study endpoint was not focused on central blood pressure and arterial stiffness estimation. Albeit, these devices offer the chance for a new attempt to compare invasive and non-invasive blood pressure monitoring on an intensive care unit.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of hemodynamic may not be related to the improvement of microcirculation (4,9). Septic shock is defined as a microcirculation disease, and many trials showed that the severity of microvascular alterations is associated with outcomes in patients with septic shock (10)(11)(12)(13)(14). Evaluation of the response for hemodynamic management is critical for the prognosis of sepsis.…”
Section: Introductionmentioning
confidence: 99%